Formulasi Krim Antibakteri Ekstrak Etanol Daun Awar-Awar (Ficus Septica Burm.) Terhadap Bakteri Staphylococcus Aureus - Iva Rinia Dewi; Arinda Nur Cahyani; Marcello Ferrel Firmansyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Skin infection is a disease caused by microorganisms, one of which is Staphylococcus aureus bacteria. Treatment of skin infections can be done by using topical antibacterials such as creams. Previous studies have shown that awar-awar leaves have antibacterial activity against S. aureus. The purpose of this study was to determine the awar-awar leaf extract (Ficus septica Burm.) can be formulated as an active substance in cream preparations and to determine the preparation of awar-awar leaf extract cream (Ficus septica Burm.) has antibacterial activity against S. aureus bacteria. This research was conducted at the Microbiology and Pharmaceutical Technology Laboratory of STIKes Ibnu Sina Ajibarang. This type of research is experimental using wells diffusion method with concentration variation (F1=15%; F2=20%; and F3=25%). The positive control used was Gentamicin Cream (Bernofarm) and the negative control used was cream base. Parameters evaluated included antibacterial inhibition zone diameter, cream organoleptic, homogeneity, pH, spreadability, cream type, adhesiveness and cream stability. The results showed that the cream formulation made had met the criteria of the physical examination for cream formulations. The resulting cream formulation was homogeneous, had a pH range of 5 - 6, a spreadability of 5.135 cm to 5.177 cm, an oil-in-water cream type, and cream adhesion ranging from 2.45 seconds - 3.28 seconds. The antibacterial activity of cream formulations against S. aureus in F1, F2, and F3 were 2.46 mm, 3.29 mm, 5.44 mm respectively. Formulations F1 and F2 are classified as weak antibacterial while formulation F3 is classified as moderate antibacterial.